APP family member dimeric complexes are formed predominantly in synaptic compartments - Schilling, Sandra; August, Alexander; Meleux, Mathieu; Conradt, Carolin; Tremmel, Luisa M.; Teigler, Sandra; Adam, Virginie; Müller, Ulrike C.; Koo, Edward H.; Kins, Stefan; Eggert, Simone (Cell & bioscience, 2023)
The amyloid precursor protein (APP), a key player in Alzheimer’s disease (AD), is part of a larger gene family, including the APP like proteins APLP1 and APLP2. They share similar structures, form homo- and heterotypic dimers and exhibit overlapping functions.